Pengembangan Aplikasi Pendeteksi Kantuk Pada Pengendara Kendaraan Bermotor Dengan Menggunakan Sensor Detak Jantung Pada Smartwatch - Imam Farouqi Faisal; Agi Putra Kharisma; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The majority of traffic accidents that occur are caused by human error, one of which is drowsy. When drowsy, the driver's concentration tends to decrease, so it can cause loss of control over the vehicle, this can lead to traffic accidents. Therefore, there's a need for a solution that can prevent traffic accidents caused by drowsiness. Based on these problems, the author offers a system that can detect driver drowsiness, so if the driver is drowsy, he can be given a warning immediately. This system is an Android based application that uses heart rate data to detect drowsiness. To obtain heart rate, this application is using the heart rate monitor sensor on the smartwatch which the driver must wear. In its development, this application is designed using Object Oriented Design (OOD) approach and implemented using Object Oriented Programming (OOP) method. Black box, accuracy, and usability are tested. Black box testing result shows that this application has 100% validity rate, based on accuracy testing conducted on five respondents, this application has 86,3% accuracy rate, showing that this application can detect the respondents' drowsiness accurately, whereas based on usability testing, this application has 83,5 score which means it got B (Excellent) rate.